Alexithymia and sensory processing sensitivity account for unique variance in the prediction of emotional contagion and empathy - McQuarrie, Amanda M.; Smith, Stephen D.; Jakobson, Lorna S. (Frontiers in Psychology, 2023)
Introduction Empathy—the ability to identify and share another person’s emotional state—is an important socio-emotional process arising, in part, from emotional contagion. In the current study, we assessed unique variance in emotional contagion and other empathy-related constructs accounted for by two personality traits, alexithymia and sensory processing sensitivity (SPS), when controlling for childhood emotional abuse and current depressed mood. Methods A sample of 305 adults (Mage = 20.1 years) watched brief film clips chosen to induce various emotional states. After each film, the participants rated how strongly they experienced each of nine different emotions. They then completed self-report measures of alexithymia, SPS, empathy-related constructs, childhood emotional abuse, and current mood. Results Those scoring high (vs. low) on SPS reported stronger primary emotions and a larger range of emotions when watching the films and were more apt to believe that their emotions matched those of the individuals featured in the films. They also scored higher on both self-oriented processes (such as the tendency to feel personal distress in tense situations) and other-oriented processes (such as perspective taking and empathic concern) related to empathy. Individuals scoring high (vs. low) on alexithymia reported feeling a larger range of emotions while watching the films but scored lower on other-oriented processes related to empathy. After controlling for SPS and alexithymia, current depressed mood predicted experiencing less varied reactions to mixed valence films that elicited strong feelings of embarrassment/humiliation, and less amusement when watching positive films. Childhood emotional abuse did not emerge as a predictor of emotional contagion or empathy. Discussion We propose that the strong and nuanced feelings elicited in those scoring high on SPS by observing others support their personal view that they are highly empathic. In contrast, by failing to closely examine their own mixed reactions to others, individuals with alexithymia may find it difficult to connect with, understand, and respond to others’ feelings.